2018
DOI: 10.1142/9789813232754_0013
|View full text |Cite
|
Sign up to set email alerts
|

Does Ownership Matter? Empirical Evidence from the German Wine Industry

Abstract: the editor) and the referees for their detailed and valuable comments that helped to improve the paper. Moreover, I am indebted to Joachim Prinz for his research assistance and to Lucas Bretschger, Helmut Dietl and Hans Hirth for suggestions and recommendations. All remaining errors are, of course, my own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…These wine ratings range from “unacceptable” (those nearer to 50) to “extraordinary” (those closer to 100). This type of information is frequently used in the literature to rate quality (e.g., Benjamin & Podolny, 1999; Cacchiarelli et al, 2016; Castriota & Delmastro, 2012; Costanigro, McCluskey, & Goemans, 2010; Frick, 2004; Landon & Smith, 1998; López‐Bayón et al, 2018; Pennerstorfer & Weiss, 2013; Schamel & Anderson, 2003; Scott‐Morton & Podolny, 2002). The advantage of this type of information is that professional guides employ experts to rate wines and force them to follow highly systematized procedures and rigorous standards of evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…These wine ratings range from “unacceptable” (those nearer to 50) to “extraordinary” (those closer to 100). This type of information is frequently used in the literature to rate quality (e.g., Benjamin & Podolny, 1999; Cacchiarelli et al, 2016; Castriota & Delmastro, 2012; Costanigro, McCluskey, & Goemans, 2010; Frick, 2004; Landon & Smith, 1998; López‐Bayón et al, 2018; Pennerstorfer & Weiss, 2013; Schamel & Anderson, 2003; Scott‐Morton & Podolny, 2002). The advantage of this type of information is that professional guides employ experts to rate wines and force them to follow highly systematized procedures and rigorous standards of evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…This involves things as pricing, e.g., prices are not always differentiated based on quality and quantity, and member control, e.g., the general rule is that all members have equal voting rights". Finally, the evidence regarding the relationship between governance structure and product quality in agricultural markets indicates that there are many cooperatives providing low quality products (Frick, 2004;Theodorakopoulou and Iliopoulos, 2012;Bijman et al, 2012;Pennerstorfer and Weiss, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, a large proportion of Ontario wineries are owner operated rather than having professional managers. The lack of management competency putting into question their projected growth plans is consistent with the findings of Frick (2004) who found that wineries that are run by professional managers are more profitable as a result of their better management competency. It would be interesting to see in two years how many wineries achieve their growth objectives.…”
Section: Discussionsupporting
confidence: 84%
“…The (Burton & Jacobsen, 2001), the effects o f who operates a wineryprofessional manager or owner (Frick, 2004), the motivation (utility and/or profit) of winery owners (Morton and Podolny, 2002), the relationship o f quality and grape growing contracts (Goodhue et al, 2003), the relationship between social order, status and quality amongst wineries (Benjamin & Podolny, 1999) as well as several studies of wine clusters that will be described in more detail later. Some o f these papers do have relevance to the current study.…”
Section: Business Of Wine Literaturementioning
confidence: 99%
See 1 more Smart Citation